2013
DOI: 10.1002/rnj.69
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interactions with Providers on Stroke Caregivers' Needs

Abstract: Purpose Preparation for caregiving is improved through engaged interactions between stroke family caregivers and healthcare providers throughout the care trajectory. We explored caregivers’ perceptions about interactions with providers in rehabilitation, and how these experiences affected caregiver preparation. Design Seventeen caregivers, included in this grounded theory study, were interviewed during a rehabilitation stay and post-discharge. Data were analyzed using dimensional and comparative analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 34 publications
3
75
0
Order By: Relevance
“…Health care providers consistently considered the patient as the primary focus of care. However, caregivers also wanted to receive support, beginning from the discharge (preparation) to the post-discharge (adaptation) phases [18], a finding consistent with other studies [8, 9, 15, 16]. …”
supporting
confidence: 56%
See 2 more Smart Citations
“…Health care providers consistently considered the patient as the primary focus of care. However, caregivers also wanted to receive support, beginning from the discharge (preparation) to the post-discharge (adaptation) phases [18], a finding consistent with other studies [8, 9, 15, 16]. …”
supporting
confidence: 56%
“…This finding underscores the need for early caregiver assessment followed by individualized caregiver interventions during these critical time periods following stroke [19, 27, 28]. Results in Creasy et al’s [16] study showed it was important to caregivers that information about stroke was presented in a timely fashion and was applicable to the person with stroke, and also that health care providers emphasized the importance of this information to the caregivers. Cameron et al’s 2013 [18] and 2014 [36] studies using the “Timing it Right” framework illustrated how stroke caregivers’ needs for information and support change over time.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Uncertainty is a further common theme found within the caregiver qualitative research (Greenwood, MacKenzie, Wilson, & Cloud, 2009b), coupled with poor communication from healthcare providers and lack of stroke specific information and discharge needs not being met (Camak, 2015;Creasy, Lutz, Young, Ford, & Martz, 2013). However, previous research identifying uncertainty underling the caregiving experience has focused on caregivers of stroke survivors recently discharged up to 3 months post-discharge (Greenwood et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…They are concerned about not having the necessary skills which are required for optimal care given to their partners. Creasy et al (2013) conducted a study of 17 family caregivers of stoke patients and their interaction with physicians. The study found that caregivers felt very disconnected and ignored by physicians and there was a lack of communication between each other.…”
Section: Caregiver’s Burdenmentioning
confidence: 99%